Nilai-Nilai Pendidikan Tasawuf Akhlaki dalam Novel Biografi “Surat Cinta Para Sufi” Karya Mohamad Fathollah - Choiriyatul Aiyun; Ali Muhsin; Andik Wahyun Muqoyyidin (INDO PUBLISHING, 2026)
This study aims to analyze, identify, and examine in depth the educational values ​​of Sufism Akhlaki contained in the biographical novel “Surat Cinta Para Sufi” by Mohamad Fathollah. This study uses a descriptive qualitative method with a library research approach and content analysis. Data were collected through careful reading of the novel text, identifying parts relevant to the concept of Sufism Akhlaki, and classifying them based on predetermined educational value categories. The results of this study indicate that the novel “Surat Cinta Para Sufi” contains a variety of rich educational values ​​of Sufism Akhlaki, including aspects such as mahabbah (divine love), zuhud (simplicity and not being tied to the world), mujahadah an-nafs (fighting lust), gratitude, tawakal, muhasabah (self-introspection), and the importance of the guidance of the mursyid. Sufi thought reflects Sufism Akhlaki which emphasizes the formation of the soul through the values ​​of divine love, patience, and sincerity. Sufi thought is depicted between vertical dimensions (relationship with God) and horizontal dimensions (relationships with others). This is relevant to the problems of contemporary Islamic education, namely the moral crisis and the culture of luxurious living. The conclusion of this study is that the biographical novel